Resilience of Dreissena polymorpha in wastewater effluent: Use as a bioremediation tool?. (15th January 2021) - Géba, Elodie; Rioult, Damien; Palluel, Olivier; Dedourge-Geffard, Odile; Betoulle, Stéphane; Aubert, Dominique; Bigot-Clivot, Aurélie
Abstract: Nowadays, it is necessary to improve the efficiency of wastewater treatment plant treatments. In this context the use of biofilter species, like Dreissena polymorpha, as a bioremediation tool in wastewater is increasingly highlighted. The innovative aim of this study is to evaluate the zebra mussel survival in the outlet channel of a conventional WWTP to use them as bioremediation tool. For this, mussels were transplanted in the outlet channel for 28 days and different biomarkers were monitored. D. polymorpha is able to maintain itself in good physiological conditions until 21 days, yet at 28 days a high mortality rate (24%), a decrease in filtration efficiency (8/15 mussels filtered and 17.0% of filtration rate) and antioxidant system activation (CAT activity et gpx gene expression increase) suggest an exhaustion. Some biomarkers suggested a hypoxic stress. Despite the unfavourable conditions, bivalves have bioaccumulated pathogenic protozoa ( Toxoplasma gondii and Giardia duodenalis ) during the exposure. Zebra mussel seems to be a promising tool for bioremediation in wastewater. Graphical abstract: Image 1 Highlights: Dreissena polymorpha maintained in good health until 21days in wastewater. Some biomarkers suggested a hypoxic stress in outlet channel of WWTP at 28 days. Zebra mussel have bioaccumulated pathogenic protozoa during the exposure. D. polymorpha seems to be a promising tool for bioremediation in wastewater.